HUBUNGAN LITERASI MEDIA DENGAN TINGKAT AKSES KURSUS PROGRAM PENDIDIKAN ONLINE LINKEDIN LEARNING MAHASISWA FAKULTAS ILMU KOMUNIKASI NON-PASCASARJANA UNIVERSITAS PADJADJARAN - Ilyas, Januar; Rizal, Edwin; Yanto, Andri (Program Studi Perpustakaan dan Ilmu Informasi, Fakultas Bahasa dan Seni, Universitas Negeri Padang, 2024)
This study aims to see if there is a relationship between media literacy and the level of access to LinkedIn Learning courses. The concept of digital literacy used in the research is the Individual Competence Framework by the European Commission which consists of 3 indicators, namely technical usage skills, critical understanding, and communication skills. The media literacy variable is further divided into 3 (three) ability categories namely Basic, Medium, and Advanced. Similarly, the LinkedIn Learning course access variable is divided into 3 (three) levels namely “Low”, “Medium”, “High”. The method used in this research is a quantitative method with a correlational approach, which tries to see the relationship between two or more variables and the strength of the relationship. This research was conducted on 65 students of the Faculty of Non-Postgraduate Communication Sciences class of 2019, 2020, 2021 and 2023 at Padjadjaran University, who were selected based on simple random sampling technique. The data analysis techniques used in this study are descriptive and inferential using the Chi-Square test. The results showed that there was no correlation between students' media literacy and the level of access to LinkedIn Learning online education program courses by students of the Faculty of Non-Postgraduate Communication Sciences, Universitas Padjadjaran. From the three sub-variables of media literacy based on the Individual Competence Framework, namely critical understanding, and communication skills also have a significant relationship with media literacy, but the sub-variable of technical usage skills has a significant relationship with media literacy.